Lung cancer risk in workers exposed to poly(vinyl chloride) dust: a nested case-referent study. Issue 6 (1st June 2003) - Mastrangelo, G; Fedeli, U; Fadda, E; Milan, G; Turato, A; Pavanello, S
Abstract : Background: There have been few investigations of an association between poly(vinyl chloride) (PVC) dust exposure and an increase in lung cancer incidence, and their conclusions have been inconsistent. Aims: To determine whether PVC and/or vinyl chloride monomer (VCM) is the associated risk factor(s), by means of a nested case-referent study, in order to estimate lung cancer risk, avoiding selection, information, or confounding biases. Methods: Thirty eight cases of histologically verified lung cancer and 224 control subjects without a history of cancer were selected from an Italian cohort of 1658 vinyl chloride workers. Information sources included clinical records (diagnosis, smoking habits) and plant records (occupational history). The risk of lung cancer was estimated by odds ratios (OR) with 95% confidence intervals (CI), calculated using logistic regression models. Results: In PVC baggers exposed to high levels of respirable PVC particles in the workplace, the lung cancer OR increases by 20% for each extra year of work (OR = 1.2003; 95% CI 1.0772 to 1.3469; p = 0.0010), when the influence of age and smoking habits is controlled. No relation was found between lung cancer and cumulative VCM exposure. Conclusion: This nested case-control study showed, in the VCM/PVC industry, an increased risk of lung cancer associated with exposure to PVC dust; previous cohort studies failed to recognise such excess, probably because they used VCM exposure as the risk indicator.